The Concerted Action of E2-2 and HEB Is Critical for Early Lymphoid Specification - Bouderlique, Thibault; Peña-Pérez, Lucia; Kharazi, Shabnam; Hils, Miriam; Li, Xiaoze; Krstic, Aleksandra; De Paepe, Ayla; Schachtrup, Christian; Gustafsson, Charlotte; Holmberg, Dan; Schachtrup, Kristina; Månsson, Robert (Frontiers in Immunology, 2019)
The apparition of adaptive immunity in Gnathostomata correlates with the expansion of the E-protein family to encompass E2-2, HEB and E2A. Within the family, E2-2 and HEB are more closely evolutionarily related but their concerted action in hematopoiesis remains to be explored. Here we show that the combined disruption of E2-2 and HEB results in failure to express the early lymphoid program in CLPs and a near complete block in B-cell development. In the thymus, ETPs were reduced and T-cell development perturbed, resulting in reduced CD4 T- and increased γδ T-cell numbers. In contrast, HSCs, erythro-myeloid progenitors and innate immune cells were unaffected showing that E2-2 and HEB are dispensable for the ancestral hematopoietic lineages. Taken together, this E-protein dependence suggests that the appearance of the full Gnathostomata E-protein repertoire was critical to reinforce the gene regulatory circuits that drove the emergence and expansion of the lineages constituting humoral immunity.